Shared Oocyte Donation: Ideas and Expectations in a Bioethical Context Based on a Qualitative Survey of Brazilian Women - Drauzio Oppenheimer; Agatha Ramos Oppenheimer; Sthefano Teixeira de Vilhena; Augusto Castelli Von Atzingen (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective Assisted reproduction combines innovative technologies and new forms of procreation through gamete donation; however, it also leads to moral and ethical issues and to the wide application of referential bioethics. The objective of the present study was to understand the bioethical context of shared oocyte donation. Methods The present qualitative study used the Collective Subject Discourse methodology to interview donors and recipients in Brazil. Results Donors suffer from infertility, and in vitro fertilization opens the possibility of having a child; however, the cost is high, and helping the recipient is more important than the financial cost. The recipients regret delaying motherhood; adopting a child is their last option, and they desire to feel the physical stages of pregnancy. The recipients find the rules unfair regarding the lack of an oocyte bank and the fact that the treatment must be performed in shared cycles; however, oocyte donation makes it possible to realize the common dream of motherhood. Conclusion The obtained data showed that the patients are suffering and frustrated due to infertility, and they realize that in vitro fertilization may be the treatment they need. These women believe that children are essential in the constitution of the family, and scientific advances bring about innovative technologies and new forms of family constitution, with repercussions in the social, economic, political, and family contexts that lead to bioethical questions in Postmodernity.